TINJAUAN YURIDIS PENYELESAIAN KREDIT MACET MELALUI JALUR NON LITIGASI PADA BANK BRI (STUDI PENELITIAN BANK BRI UNIT LAMASI) - Rahman Nur, Abdul; Salmi, Salmi; Kamal, Kasmad; Goali, Fahrul (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2025)
In many developing countries, there are still many public sector institutions that do not yet have the capacity to provide good quality public services. The Provincial Government of D.I. Yogyakarta is one of the institutions that is currently intensively carrying out various public service improvements throughout innovations. One of many innovations that has been implemented is an application called Jogjaplan, which is an e-planning (electronic planning) system that is also capable in not just actualizing, but also making improvement in public participation through open access towards information and by creating a public forum for aspirations regarding development planning. This study aims to determine the role of innovation in the form of the Jogjaplan application in increasing community participation in the governance of the Province of D.I. Yogyakarta. This study uses descriptive qualitative methods with data collection techniques in the form of literature studies based on relevant books, scientific journals, news articles, and official government websites. Based on this research, Jogjaplan was proven to be capable of simplifying the planning process in terms of processing data and documents. However, the use of the Jogjaplan application in the context of public participation is still not optimal. The number of people who access and provide suggestions regarding program planning in D.I.Y is still relatively low. This is due to the lack of socialization carried out by the local government to the public which is also exacerbated by the low responsiveness of the government towards the inputs made by the public.